2017
DOI: 10.1002/adma.201702210
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectrics as Smart Mechanical Materials

Abstract: The mechanical properties of materials are insensitive to space inversion, even when they are crystallographically asymmetric. In practice, this means that turning a piezoelectric crystal upside down or switching the polarization of a ferroelectric should not change its mechanical response. Strain gradients, however, introduce an additional source of asymmetry that has mechanical consequences. Using nanoindentation and contact-resonance force microscopy, this study demonstrates that the mechanical response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…The black line marks the region where the gradient-induced electric field is strong enough to be able to induce local switching of the polarization Flexoelectric effects are proportional to dielectric permittivity [29] , therefore, it is to be expected that in a ferroelectric, with a higher dielectric constant, such as Lithium Niobate (LN) ( = 13; = 37), [30] the local flexoelectric switching is enhanced. The coercive field for LN is E c = 2.1x10 7 Vm -1 [31] , by using the flexocoupling coefficient estimated elsewhere [12] , we obtained that the strain gradient required to induce local switching is 4.2x10 5 m -1 . Using equations (5) - (8), and the values in the literature [32 -34] , we found that the distance from the crack tip that corresponds to this strain gradient is ~ 25 nm around the tip, which is big enough to be stable and detectable at room temperature.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The black line marks the region where the gradient-induced electric field is strong enough to be able to induce local switching of the polarization Flexoelectric effects are proportional to dielectric permittivity [29] , therefore, it is to be expected that in a ferroelectric, with a higher dielectric constant, such as Lithium Niobate (LN) ( = 13; = 37), [30] the local flexoelectric switching is enhanced. The coercive field for LN is E c = 2.1x10 7 Vm -1 [31] , by using the flexocoupling coefficient estimated elsewhere [12] , we obtained that the strain gradient required to induce local switching is 4.2x10 5 m -1 . Using equations (5) - (8), and the values in the literature [32 -34] , we found that the distance from the crack tip that corresponds to this strain gradient is ~ 25 nm around the tip, which is big enough to be stable and detectable at room temperature.…”
Section: Resultsmentioning
confidence: 68%
“…[11] In the case of ferroelectrics, flexoelectricity enables qualitatively new behaviours. For example, it has recently been predicted [10] and demonstrated [12] that ferroelectrics can have an asymmetric mechanical response to inhomogeneous deformations.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we report on centrosymmetry breaking induced by nanoindentations in bulk undoped SrTiO 3 . Indentations were previously exploited to induce flexoelectric effects in polar materials . After mapping the topography of the nanoindentations with atomic force microscopy (AFM), we show with Raman spectroscopy imaging that the nanoindentations generate deformations and therefore a strain gradient in their vicinity.…”
Section: Introductionmentioning
confidence: 93%
“…Unlike in the high‐temperature paraelectric phase (space group R true3¯ c ), strong internal elastic forces result in atom displacement (from the centrosymmetric position). The thus created dipoles organize themselves into domains, thereby giving rise to robust spontaneous polarization . Lithium tantalate (LiTaO 3 ) shows analogous behavior.…”
Section: Introductionmentioning
confidence: 99%